2019
DOI: 10.5935/abc.20190123
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk in Psoriasis Patients: Clinical, Functional and Morphological Parameters

Abstract: BackgroundPsoriasis correlates with metabolic disorders, early atheromatosis and increased cardiovascular risk.ObjectivesTo assess markers of cardiovascular disease in psoriatic patients.MethodsCross-sectional, observational study involving 11 psoriatic participants and 33 controls. Anthropometric, biochemical, hemodynamic and imaging parameters were evaluated. Arterial stiffness was assessed by oscillometric measurement of the brachial artery. Intima-media thickness (IMT) and left ventricular diastolic functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…Thus, several studies have shown changes in AIx@75 without signi cant changes in PWV in children, which corroborates our ndings [13,14,18,20]. The inverse of this process occurs in older individuals, where PWV increases and AIx changes slightly, which suggests that the increase in AP would be driven by an earlier return of the re ected wave and a less compliant aorta rather than predominant changes in the magnitude of wave re ection [12,40]. It is expected that in situations where there is an increase in AIx, the DBPc will be reduced, as was observed in our study of the APG.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, several studies have shown changes in AIx@75 without signi cant changes in PWV in children, which corroborates our ndings [13,14,18,20]. The inverse of this process occurs in older individuals, where PWV increases and AIx changes slightly, which suggests that the increase in AP would be driven by an earlier return of the re ected wave and a less compliant aorta rather than predominant changes in the magnitude of wave re ection [12,40]. It is expected that in situations where there is an increase in AIx, the DBPc will be reduced, as was observed in our study of the APG.…”
Section: Discussionsupporting
confidence: 90%
“…Currently, efforts have been made to nd early markers of cardiovascular disease so that timeous intervention can be carried out to reduce the development and progression of cardiovascular diseases, thus highlighting the importance of investigating arterial stiffness [11]. Possible early cardiovascular risk markers include pulse wave velocity (PWV), considered a great indicator of arterial stiffness, [12] and the augmentation index normalized to a heart rate of 75 beats per minute (AIx@75), an independent predictor of future cardiovascular events and mortality [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In this regard, different techniques have been used to stratify the cardiovascular risk of patients with inflammatory skin diseases, such as carotid ultrasonography 3,4 and pulse wave velocity. 3 Regarding ultrasonography, the measurement of the intimamedia thickness (IMT) in the common carotid artery of patients with HS has been reported to be associated with higher burden…”
mentioning
confidence: 99%
“…They found that more than one-fourth of those participants had >20% probability of cardiovascular events in 10 years. Oliveira et al 8 studied 11 consecutive male patients with psoriasis (an inflammatory disorder also associated with increased cardiovascular risk 9 ) and 33 age-matched controls and found significantly higher total cholesterol, LDL-cholesterol and C-reactive protein levels and a trend towards higher frequencies of smoking and hypertension diagnosis in individuals with psoriasis compared to controls.…”
mentioning
confidence: 99%